(untitled) (Nexo Revista Científica, 2023)
Cathodic Protection System (CPS) is used on a variety of structures to prevent corrosion in ship hulls, pipelines, and underground storage tanks. Transmission pipelines extend over wide distances that may extend for hundreds of kilometers, the problem of corrosion exists in pipelines transporting liquids such as oil, petroleum or water, as well as in pipelines transporting gases. Corrosion leads to leakage into the surrounding environment, causing pollution. Artificial intelligence (AI) is used in risk management to determine the possibility of corrosion growth rates, considering all the determinants and factors that contribute to corrosion, including alternating currents, soil properties, environmental conditions, and geographical features. According to research, there are two ways to enhance the performance of cathodic protection systems: one is to design cathodic protection in unconventional ways based on different algorithms and methods that show superiority over the traditional method in determining the number and location of anodes, and the other is to continuously monitor the environmental conditions surrounding the structure to be protected, which includes soil and weather. A study will be conducted to determine the most effective factors in protecting the pipelines and other factors to determine the required energy in an efficient method.